DYE REMOVAL FROM TEXTILE WASTEWATER BY COAGULATION USING ALUM AND PAC (Journal of Engineering, 2011)
Removal of solar brown and direct black dyes by coagulation with two aluminum basedcoagulants was conducted. The main objective is to examine the efficiency of thesecoagulants in the treatment of dye polluted water discharged from Al-Kadhymia TextileCompany (Baghdad-Iraq). The performance of these coagulants was investigated throughjar test by comparing dye percent removal at different wastewater pH, coagulant dose,and initial dye concentration. Results show that alum works better than PAC under acidicmedia (5-6) and PAC works better under basic media (7-8) in the removal of both solarbrown and direct black dyes. Higher doses of PAC were required to achieve themaximum removal efficiency under optimum pH conditions for both dyes. It wasobserved that under optimum conditions of pH and dose values, PAC was significantlyhigher dye removal efficiency than alum for all dyes initial concentrations.